CAF Subpopulations: A New Reservoir of Stromal Targets in Pancreatic Cancer - Pereira, Brooke A; Vennin, Claire; Papanicolaou, Michael; Chambers, Cecilia R; Herrmann, David; Morton, Jennifer P; Cox, Thomas R; Timpson, Paul (Trends in cancer, 2019)
Cancer-associated fibroblasts (CAFs) are one of the most significant components in the tumour microenvironment (TME), where they can perform several protumourigenic functions. Several studies have recently reported that CAFs are more heterogenous and plastic than was previously thought. As such, there has been a shift in the field to study CAF subpopulations and the emergent functions of these subsets in tumourigenesis. In this review, we explore how different aspects of CAF heterogeneity are defined and how these manifest in multiple cancers, with a focus on pancreatic ductal adenocarcinoma (PDAC). We also discuss therapeutic approaches to selectively target protumourigenic CAF functions, while avoiding normal fibroblasts, providing insight into the future of stromal targeting for the treatment of PDAC and other solid tumours.